2015
DOI: 10.1007/s11682-015-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical abilities in dyslexic children: a diffusion tensor imaging study

Abstract: Dyslexia is characterized by a deficit in language processing which mainly affects word decoding and spelling skills. In addition, children with dyslexia also show problems in mathematics. However, for the latter, the underlying structural correlates have not been investigated. Sixteen children with dyslexia (mean age 9.8 years [0.39]) and 24 typically developing children (mean age 9.9 years [0.29]) group matched for age, gender, IQ, and handedness underwent 3 T MR diffusion tensor imaging as well as cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…estimating calculation results) and comparing magnitudes are separable from those supporting exact arithmetic (Dehaene, Piazza, Pinel, & Cohen, ). Especially relevant for this study are findings showing that the representation of exact arithmetic recruits language‐related networks (Dehaene et al., ; Evans, Flowers, Napoliello, Olulade, & Eden, ; Koerte et al., ) that are also involved in reading. Based on these findings, the association between literacy and exact arithmetic found in this study is to be expected and is in line with recent fMRI findings showing similar neural activation patterns in children with RD, MD and comorbid problems during arithmetic tasks (Peters, Bulthé, Daniels, de Beeck, & De Smedt, ).…”
Section: Discussionmentioning
confidence: 88%
“…estimating calculation results) and comparing magnitudes are separable from those supporting exact arithmetic (Dehaene, Piazza, Pinel, & Cohen, ). Especially relevant for this study are findings showing that the representation of exact arithmetic recruits language‐related networks (Dehaene et al., ; Evans, Flowers, Napoliello, Olulade, & Eden, ; Koerte et al., ) that are also involved in reading. Based on these findings, the association between literacy and exact arithmetic found in this study is to be expected and is in line with recent fMRI findings showing similar neural activation patterns in children with RD, MD and comorbid problems during arithmetic tasks (Peters, Bulthé, Daniels, de Beeck, & De Smedt, ).…”
Section: Discussionmentioning
confidence: 88%
“…More problematic perhaps, Keller and Just (2009) were unable to replicate these findings in an intervention study, instead reporting lower FA in an anterior region, the left anterior centrum semiovale. Similarly, Koerte et al (2016) found no significant differences in FA when controlling for false positives adequately. Studies have also found a variety of significant differences in other brain regions, including the superior and inferior frontal regions, precuneus, insula and occipital region in the left hemisphere, superior corona radiata, splenium of the corpus callosum and throughout the right hemisphere (Carter et al, 2009;Deutsch et al, 2005;Frye et al, 2008;Niogi & McCandliss, 2006;Rimrodt et al, 2010;Steinbrink et al, 2008).…”
mentioning
confidence: 91%
“…Individuals with dyslexia are known to experience particular mathematical difficulties with verbal arithmetic, likely related to impaired phonological retrieval processes (Boets & De Smedt, 2010). In this study, arithmetic efficiency showed a greater correlation with FA in children with dyslexia vs. controls in a large number of white matter tracts, including the bilateral ILF and SLF (Koerte et al, 2016).…”
mentioning
confidence: 57%
“…Although departing from some of the published literature, our results are in line with some of the prior research examining white matter tracts in dyslexic and typical readers. For example, a study by Koerte et al (2016) reported no difference between dyslexics and typical readers using various diffusion measures, after correcting for multiple comparisons. In addition, a meta-analysis by Vandermosten and colleagues (2012) yielded two clusters with a significant difference in FA between poor and typical readers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation